Effects of visual deprivation on the injury of lower extremities among functional ankle instability patients during drop landing: A kinetics perspective - Meng, Lingyue; Kong, Lintao; Kong, Lingyu; Zhang, Qiuxia; Shen, Jianzhong; Hao, Yuefeng (Frontiers in Physiology, 2022)
Background: The ankle is prone to injury during drop landing with usual residual symptoms, and functional ankle instability (FAI) is the most common. Visual guarantees the postural stability of patients with FAI, and visual deprivation (VD) increases their risk of injury when completing various movements. This study aimed to explore injury risk during drop landing in patients with FAI under VD through the kinetics of lower extremities. Methods: Twelve males with FAI participated in the study (age, 23.0±0.8 years; height, 1.68±0.06 m; weight, and 62.2±10.4 kg) and completed single-leg drop landing under visual presence (VP) and VD conditions. Ground reaction force (GRF), time to peak GRF, joint torque, and vertical length variation (ΔL), were measured. Results: Significant effects of the group were detected for time to peak lateral GRF (P =0.004), hip extensor torque (P =0.022), ankle plantarflexion torque (P＜0.001), ankle varus torque (P =0.021), lower extremity stiffness (P =0.035), and ankle stiffness (P＜0.001). Significant effects of the condition were detected for vertical GRF, time to peak vertical and lateral GRF, loading rate, hip extensor torque, knee extensor torque, hip varus torque, knee varus torque, lower extremity stiffness, and ankle stiffness (P＜0.05). ΔL was affected by VD with a significant interaction (P＜0.001). Conclusions: In patients with FAI, unstable extremity has a higher injury risk than stable extremity, and VD increases such risk. However, because the control of the central nervous system on hip strategy is also affected, the effect on unstable extremity is more significant and more likely to result in injury. Deepening the squat range may be an effective preventive measure to reduce the injury risk of unstable extremity during drop landing.